Attention-deficit/hyperactivity disorder: variation by socioeconomic deprivation. Issue 8 (30th March 2018) - Prasad, Vibhore; West, Joe; Kendrick, Denise; Sayal, Kapil
Abstract : Background: In England, there is a discrepancy between the prevalence of attention-deficit/hyperactivity disorder (ADHD) ascertained from medical records and community surveys. There is also a lack of data on variation in recorded prevalence by deprivation and geographical region; information that is important for service development and commissioning. Methods: Cohort study using data from the Clinical Practice Research Datalink comprising 5196 children and young people aged 3–17 years with ADHD and 490 016 without, in 2012. Results: In 2012, the recorded prevalence of ADHD was 1.06% (95% CI 1.03 to 1.09). Prevalence in the most deprived areas was double that of the least deprived areas (prevalence rate ratio 2.58 (95% CI 2.36 to 2.83)), with a linear trend from least to most deprived areas across all regions in England. Conclusions: The low prevalence of ADHD in medical records may indicate considerable underdiagnosis. Higher rates in more disadvantaged areas indicate greater need for services in those areas.